2015
DOI: 10.1002/ejoc.201501048
|View full text |Cite
|
Sign up to set email alerts
|

Breaking and Making of Rings: A Method for the Preparation of 4‐Quinolone‐3‐carb­oxylic Acid Amides and the Expensive Drug Ivacaftor

Abstract: A simple and convenient method to access 4-quinolone-3-carboxylic acid amides from indole-3-acetic acid amides through one-pot oxidative cleavage of the indole ring followed by condensation (Witkop-Winterfeldt type oxidation)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Following GP 6 , using 10af (120 mg, 0.36 mmol), the title compound was obtained (101 mg, 100% yield) as a yellow solid. The spectroscopic data are consistent with those previously reported . TLC: R f = 0.21 (PE:EA = 1:1).…”
Section: Experimental Sectionsupporting
confidence: 92%
“…Following GP 6 , using 10af (120 mg, 0.36 mmol), the title compound was obtained (101 mg, 100% yield) as a yellow solid. The spectroscopic data are consistent with those previously reported . TLC: R f = 0.21 (PE:EA = 1:1).…”
Section: Experimental Sectionsupporting
confidence: 92%
“…Yang's approach started from o-nitrobenzoyl acid (10a), while Laurus Pharma initiated the synthesis with o-fluoro-benzoyl acid (10b). In approach D, Vasudevan and co-authors reported the synthesis of ivacaftor using the Witkop-Winterfeldt oxidation of indolyl group 14 to form the quinoline through ozone oxidation [31,32]. For amide bond coupling with quinoline, Vertex employed aniline 5a in the initial route or 5-amino-2,4-di-tert-butylphenyl methyl carbonate (5b) in the second improved route, both derived from di-tert-butyl-phenol (15).…”
Section: Scheme 1 Disconnection Approaches For the Synthesis Of Ivaca...mentioning
confidence: 99%
“…The common denominator for three of the routes (Grohe and Heitzer [29], Gould and Jacobs [30] and Long [31]) is that they consist of ring-closure reactions to form the quinolone ring system. The fourth one (Reddy) utilizes oxidative ring cleavage of the indole ring followed by condensation [32]. Some of these routes suffer from harsh reactions conditions and there is clearly room for novel methods complementary to those already present.…”
Section: Introductionmentioning
confidence: 99%